Transmission of Mycoplasma bovis infection in bovine in vitro embryo production - Pohjanvirta, Tarja; Vähänikkilä, Nella; Mutikainen, Mervi; Lindeberg, Heli; Pelkonen, Sinikka; Peippo, Jaana; Autio, Tiina (Elsevier BV, 2023)
Mycoplasma bovis (M. bovis) causes several costly diseases in cattle and has a negative effect on cattle welfare. There is no effective commercial vaccine, and antimicrobial resistance is common. Maintaining a closed herd is the best method to minimize the risk of introduction of M. bovis. Assisted reproduction is crucial in a closed herd to make genetic improvements. M. bovis has been found in commercial semen, and contaminated semen has been the source of disease in naïve dairy herds. The objective of this study was to evaluate M. bovis transmission in bovine in vitro embryo production (IVP) using several possible exposure routes. We used a wild-type M. bovis strain isolated from semen at a final concentration of 106 CFU/mL to infect cumulus–oocyte complexes, spermatozoa, and 5-day-old embryos. We also used naturally contaminated semen in fertilization. Blastocysts were collected on day 7–8 and zona pellucida (ZP)-intact embryos were either washed 12 times, including trypsin washes as recommended by the International Embryo Technology Society (IETS), or left unwashed. Washed and unwashed embryos, follicular fluids, maturation medium, cumulus cells, fertilization medium, and G1 and G2 culture media, as well as all wash media were analyzed using enrichment culture followed by real-time PCR detection of M. bovis. Altogether, 76 pools containing 363 unwashed embryos and 52 pools containing 261 IETS washed embryos were analyzed after oocytes, spermatozoa, or 5-day-old embryos were infected with M. bovis or naturally contaminated semen was used in fertilization. We could not detect M. bovis in any of the embryo pools. M. bovis was not found in any of 12 wash media from different exposure experiments. M. bovis did not affect the blastocyst rate, except when using experimentally infected semen. Contrary to an earlier study, which used a cell co-culture system, we could not demonstrate M. bovis in embryo wash media or tight adherence of M. bovis to ZP-intact embryos. Naturally infected semen did not transmit M. bovis to embryos. We conclude that by using our IVP system, the risk of M. bovis transmission via IVP embryos to recipient cows is very low.
Keywords: nautaeläimet; alkioiden laboratoriotuotanto; siemenneste; keinollinen lisääntyminen; tarttuminen; Mycoplasma bovis; Bovine; In vitro embryo production; Semen; Assisted reproduction; Transmission